Two Graves from Batina: An indication of the economic role and social status of women near the Danube in the Early Iron Age - Ložnjak Dizdar Daria; Metzner-Nebelsick, Carola; Rajić Šikanjić Petra; Barbir, Antonela; Fileš Kramberger Julia Katarina (Arheološki vestnik, 2023)
The majority of the Early Iron Age cremation graves of women near the Middle Danube in northeast Croatia and northwest Serbia, in the cemeteries of Batina, Dalj, Vukovar, Sotin and Doroslovo, contained an urn, a set of ceramic vessels, and sometimes costume accessories and additional jewellery items, such as hair bands, pendants, or fibulae. The present paper uses interdisciplinary analysis and interpretation to examine the chronology of graves 101 and 105 from the cemetery of Batina and the role of the women in the community that lived on the site in the Early Iron Age.